The Influence of Product Design, Price, and Service Quality on Purchase Decisions in Laluv Buket Home Business in Nganjuk Regency - Faiza, Lisa Dwi Nur; Ratnanto, Sigit (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research Objectives: This study aims to determine whether product design, price, and service quality affect consumers' decisions in purchasing products at Laluv Buket's home business in Nganjuk Regency. Design/ Method/ Approach:  This study uses a causality quantitative method with non-probable techniques, especially purposive sampling with respondents being buyers of Laluv Buket in the last 6 months without limiting the domicile of 40 respondents who will be analyzed performing validity analysis, reality tests, classical statistical diagnostics, coefficient determination, and multiple linear regression tests as well as hypothesis tests with SPSS version 23 research tools. Research Findings: The outcome of this study reveals that product design, price, and service quality exert a meaningful influence and simultaneous role in shaping purchasing decisions in Laluv Buket's home business in Nganjuk Regency. Theoretical Contribution/Originality of Research: This research contributes to factors that affect purchasing decisions, especially in the bouquet business, with aspects that affect product design, price, and service quality. This is expected to add literature in understanding consumer behavior, especially in local areas. The novelty of this study lies in the combination of three independent variables, namely product design, price, and service quality on purchasing decisions and research objects in local areas such as home businesses that have rarely been researched by previous research. Practical/Policy Implications: This study provides practical suggestions for Laluv Buket's home business in Nganjuk Regency. Research Limitations: This study only focuses on Laluv Buket's home business so that the results found are not completely the same as other similar businesses in urban areas. In addition, this study only focuses on three independent variables in determining purchasing decisions, namely product design, price, and service quality. In the next study, it is expected to add variables such as promotion and location for more relevant results.